An efficient Nb-modified BiVO4 film for photo-induced bacterial inactivation and photocatalytic removal of organic pollutants. (4th April 2018) - Monfort, Olivier; Dworniczek, Ewa; Satrapinskyy, Leonid; Seniuk, Alicja; Nyblova, Daniela; Plesch, Gustav
Abstract : For the first time, Methicillin-resistant Staphylococcus aureus (MRSA) was inactivated using a Nb-modified BiVO4 photocatalyst. Abstract : Using a Nb-modified BiVO4 film, the photo-induced properties in Methicillin-resistant Staphylococcus aureus (MRSA) inactivation under simulated solar light reached 43% after 1 hour of irradiation, while 72% of Rhodamine B was degraded after 3 hours. To evaluate the efficiency of Nb–BiVO4, its photo-performance was compared with that of BiVO4 /TiO2 composites and pure BiVO4 .